Corporate social responsibility (CSR) and black economic empowerment (BEE) in South Africa: a case study of German transnational corporations - Tatjana Chahoud; Maren Kneller; Kristof Krahl; Jakob Rieken; Vera Riffler (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
This study examines the role of Corporate Social Responsibility (CSR) and Broad-Based Black Economic Empowerment (BBBEE) approaches in South Africa for the country's transformation process towards a more sustainable and equitable development. The main focus of the empirical part of the survey is on the contribution of German Transnational Corporations (TNCs) and their various stakeholders. To identify the contribution of CSR and BBBEE by German TNCs and their stakeholders the following issues are discussed: (i) South Africa's socio-economic background; (ii) The concept of “Affirmative Action” and CSR/BBBEE approaches; (iii) The Legal Framework, verification mechanism and challenges; (iv) BBBEE and CSR – opportunities and challenges from the stakeholder's perspective; (v) BBBEE and CSR – activities and perspectives of German TNCs operating in South Africa. On the basis of the survey's findings the study comes to the conclusion, that despite the various shortcomings in the ongoing implementation of the BBBEE agenda, the underlying concept is an interesting and innovative approach, which is making its own considerable contribution to South Africa's transformation strategy.
Keywords: 330; Corporate Social Responsibility; Ethnische Diskriminierung; Schwarze Menschen; Multinationales Unternehmen; Südafrika; Deutschland